Competitive Analysis of Sales and Profit Data Between ALFAMART and INDOMARET - Saepuloh, Yeyep; Noviardiansyah, Fajar (Maksi, 2024)
Indonesia, as the largest archipelagic nation with a substantial population, represents a lucrative market for the retail industry, particularly minimarkets. This study aims to analyze the sales strategies and financial performance of two dominant players in Indonesia’s minimarket retail industry: PT. Sumber Alfaria Trijaya (Alfamart) and PT. Indomarco Prismatama (Indomaret). The research employs a quantitative approach, utilizing secondary data analysis, which includes financial statements, sales data, and profit metrics from both companies. The findings reveal that while Indomaret excels in the number of outlets and service reach, Alfamart achieves higher profitability. Alfamart’s competitive advantage is attributed to its strategic expansion policy, emphasizing the establishment of outlets in major urban areas with higher market potential. Conversely, Indomaret’s expansion into remote regions has proven less effective in maximizing profitability. The study recommends that Indomaret’s management reassess its expansion strategy to enhance operational efficiency and effectiveness in the future. These findings provide valuable insights for retail industry stakeholders in formulating business strategies aimed at optimizing profitability.